Reseña sobre: Indigenous agency in the Amazon: the Mojos in liberal and rubber-boom Bolivia, 1842-1932, de Gary Van Valen (2013) (Memoria Americana. Cuadernos de Etnohistoria, 2013)
Reseña sobre el libro escrito por Gary Van Valen (2013) titulado Indigenous agency in the Amazon: The Mojos in liberal and rubber-boom Bolivia, 1842-1932. Tucson, The University of Arizona Press.